Design, characterization and cellular uptake studies of fluorescence-labeled prototypic cathepsin inhibitors1. Issue 41 (7th November 2015) - Kohl, Franziska; Schmitz, Janina; Furtmann, Norbert; Schulz-Fincke, Anna-Christina; Mertens, Matthias D.; Küppers, Jim; Benkhoff, Marcel; Tobiasch, Edda; Bartz, Ulrike; Bajorath, Jürgen; Stirnberg, Marit; Gütschow, Michael
<x xml:space="preserve">Abstract</x> Cysteine cathepsin inhibition and cellular uptake of a coumarin 343-containing dipeptide nitrile was analyzed.